Validity and Reliability of the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form and Its Correlation With Urodynamic Findings - Hajebrahimi, Sakineh; Nourizadeh, Davoud; Hamedani, Roghayeh; Pezeshki, Mohammad Zakaria (Urology Journal, 2012)
PURPOSE: To validate the Persian version of the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF) as a standard questionnaire for assessment of urinary incontinence (UI). MATERIALS AND METHODS: After translation and back translation of the questionnaire, the harmonized translation was pre-tested in a pilot study on 28 patients. The final Persian version of the ICIQ-UI SF was administered to 123 consecutive patients aged ≥ 16 years complaining of UI. The psychometric aspects of the questionnaire, such as reliability and construct validity, were assessed and compared with full urodynamics study’s findings as the gold standard diagnostic test. RESULTS: Mean age of the participants was 46.30 ± 13.14 years (range, 16 to 72 years). Based on ICIQ-UI SF, the prevalence of mixed urinary incontinence, stress urinary incontinence and urgency urinary incontinence was 35%, 34.1%, and 30.9%, respectively. Cronbach’s alpha coefficient was calculated 0.75, which indicates the high reliability of this questionnaire in determination of UI. The obtained Weighted Kappa Index in determining the value of the test-retest was 0.70, and Pearson Correlation Coefficient was calculated 0.93 and intra-class correlation coefficient was 0.84. CONCLUSION: Persian version of ICIQ-UI SF is a simple, valid, and reliable method for evaluation of patients with UI. Significant correlation exists between ICIQ-UI SF score and urodynamics parameters.